Eliciting vulnerable consumers’ preferences for redundant vs. organic and functional claims: Experimental auction studies among young and older adults - László Bendegúz Nagy; Riccardo Vecchio; Gerarda Caso; Burak Atilla Eren; Brigitta Unger-Plasek; Zoltán Lakner; Laura Pfeiffer; Orsolya Tompa; Zsuzsánna Bogóné Tóth; Bianka Bognár; Orsolya Fehér; Ágoston Temesi (Journal of Agriculture and Food Research, 2024)
The growing use of redundant claims on food products pose a risk for organic and functional food producers among others, as it can mislead consumers in their products’ evaluations. Redundant claims refer to marketing statements that highlight qualities or attributes that are expected or should be inherent to the product. Previous studies reveal that consumers are generally willing to pay more for redundantly claimed products. In this study, preferences are analyzed for organic, functional, and redundantly labeled apple juice among specific consumer groups, namely young and old adults. To elicit individual monetary preferences a lab experiment and a field study were conducted with 147 younger (average age: 21 years) and 131 older participants (average age: 70 years), in both studies an incentive compatible technique was applied. Results showed that either younger and older consumers are willing to pay higher prices for organic, functional, and redundantly claimed apple juices. Perceived healthiness was a significant factor in increasing preferences for all the added valued products in the case of younger participants, but health only influenced preferences of organic and functional apple juice among older participants. Preferences of redundantly claimed and organic products were similar in the case of young participants, as functional and redundantly claimed juices preferences in the case of older participants.